Presença boliviana na cidade de São Paulo: da imigração à produção do espaço simbólico - Petrohilos, Ludmila Santos (2014)
The purpose of this study is to examine the uniqueness and particularity of the Bolivian presence in the city of São Paulo, through its integration with places, especially with Kantuta Square, located in the district of Pari. In addition, to elapse in the perception of space as social production and its manifestations in quotidian practices of life. This study analyzes the Bolivian behavior and language, into the city, based on a solid and abstract view. For this Geographic immersion It was adopted as essence theory of space, territory, place and landscape. For the subjective production that is established in places of conviviality, the work promotes a dialectic between other knowledge, as well as other categories such as culture and identity. Use is made of Philosophy, Sociology, Anthropology and History of the intention to establish by the Geography enriching the discussion. The adopted to bias the analysis presented here corresponds to the recognition of the causes that make immigration a matter of international order as well as the historical-geographical process that culminated in the Bolivian immigration to Brazil and, more intensely, in the city of São Paulo. From this spatialization of the problem, the research discusses the importance of places of conviviality as squares, for the manifestation of culture, the expressions of territoriality and the everyday experiences while practicing and hopes